2015
DOI: 10.1016/j.jweia.2015.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Including trees in the numerical simulations of the wind flow in urban areas: Should we care?

Abstract: a b s t r a c tAlthough trees are numerous in urban areas, their dynamic effects on the wind flow are usually approximated or neglected altogether in many wind engineering studies, especially those based on numerical modeling. This study investigates the effect of the inclusion of trees in numerical simulations of wind flow in urban area. Three approaches are used to include the dynamic effect of trees: the basic approach (tree effects are neglected), the implicit approach (tree effects are included in the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(30 citation statements)
references
References 17 publications
1
29
0
Order By: Relevance
“…This scheme is based on an equation for the turbulent kinetic energy, and it is closed with a mixing length. This is parameterized in TEB on the basis of the work by Santiago and Martilli (2010) according to the height of buildings, the mean frontal area density, and the displacement height, i.e., parameters depending on the geometry of the canyon (see Eqs. 10-12 in Lemonsu et al, 2012).…”
Section: Principle Of the Surface Boundary Layer Parameterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…This scheme is based on an equation for the turbulent kinetic energy, and it is closed with a mixing length. This is parameterized in TEB on the basis of the work by Santiago and Martilli (2010) according to the height of buildings, the mean frontal area density, and the displacement height, i.e., parameters depending on the geometry of the canyon (see Eqs. 10-12 in Lemonsu et al, 2012).…”
Section: Principle Of the Surface Boundary Layer Parameterizationmentioning
confidence: 99%
“…These fine scales are suitable for studying the airflow and dispersion processes in the street using computational fluid dynamics (CFD) models. In this configuration, trees are positioned as porous obstacles (Bruse and Fleer, 1998;Salim et al, 2015) that slow down and modify the flow. For models such as SOLENE (Miguet and Groleau, 2007), DART (Gastellu-Etchegorry et al, 1996), or SOLWEIG (Lindberg and Grimmond, 2011), mainly dedicated to radiative transfer, trees are resolved explicitly and described as turbid objects that intercept, transmit, absorb, and emit radiation in complex interactions between all surrounding objects of the scene.…”
Section: Introductionmentioning
confidence: 99%
“…Carpentieri and Robins [28] considered the wind flow shape and dispersion from the building until neighborhood scale. Salim et al [29] investigated the dynamic effect of trees on simulated wind flows in an urban area using three approaches. Kenjeres and Kuile [30] also considered the effects of vegetation on wind flow.…”
Section: General Cfd Overviewmentioning
confidence: 99%
“…At present, trees are characterized by two methods, including the implicit approach, in which the damping effects of trees are represented by the surface parameters, and the explicit approach, in which trees are modelled by porous media. Salim et al [3] studied the effects of the inclusion of trees in the numerical simulation of wind flow in urban areas with different approaches. They found that the numerical results obtained by implicit and explicit approaches are obviously different.…”
Section: Introductionmentioning
confidence: 99%